Teachers' perspective on perceived barriers to psychological well-being: a qualitative study in Sarawak - Chan, Siaw Leng; Lim, Fong Peng (Human Resource Management Academic Research Society, 2023)
Globally, restructuring and reformation of the education system have led to growing stress to perform among teachers. Assessing psychological well-being is vital to enhancing personal growth and mental wellness in the teaching-learning process. The current study aimed to understand the subjective perspectives on perceived barriers to psychological well-being among secondary school teachers. A consensual qualitative research method was applied in this study. Data was collected through in-depth, semi-structured interviews. To understand the participants' narrative perspectives better, in-depth interviews were utilized to examine the meaning of their experiences, beliefs, and values. Through purposive sampling, seven secondary school teachers were recruited. The collected data were analyzed using an open coding process to derive themes from the participants. Seven themes emerged from the study: negative parents' and students' attitudes, managerial responsibilities, inadequate school facilities, unsupportive colleagues, poor self-management, poor reputed teaching profession, and discouraging teaching experiences. The study highlighted the practical alternative to enhance teachers' psychological well-being, mental health management, and psychotherapy practice. Future research was also discussed in this study.